Preparation and cytotoxicity toward cancer cells of mono(arylimino) derivatives of β-lapachone - Di Chenna, Pablo Hector (2001)
A regio- and stereospecific synthesis of monoarylimino o-quinones derived from β-lapachone (1) was achieved by treatment of the quinone with a slight excess of an arylamine in the presence of an excess of triethylamine/titanium tetrachloride 4:1. Imine formation occurred exclusively at position 6, giving the Z diastereomer, as determined by single-crystal X-ray analysis. In vitro tests for cytotoxicity in 55 human cancer cell cultures showed a substantial loss in activity for the p-nitrophenylimine (5), whereas the phenylimine (2), p-methylphenylimine (3), and p-methoxyphenylimine (4) retained (or bettered) most of the cytotoxicity and selectivity of the parent quinone. Preliminary in vivo testing in hollow fiber assays against a standard panel of 12 human tumor cell lines showed that although β-lapachone failed, compounds 2 and 3 had good scores with net cell kills.